Effects of calcium salt of palm fatty acid supplementation on production performance, nutrient utilization and blood metabolites in Surti buffaloes (Bubalus bubalis) - RAVAL, A P; SORATHIYA, L M; KHARADI, V B; PATEL, M D; TYAGI, K K; PATEL, V R; CHOUBEY, M (The Indian Journal of Animal Sciences, 2017)
Objective of the study was to investigate the effect of dietary supplementation of rumen protected fat on productive performance, nutrient utilization and blood biochemical profile of Surti buffaloes. Eighteen multiparous buffaloes (2-4 lactation) in early lactation were divided in three homogenous groups of CON (control), BF100 and BF200 with six animals in each group. The animals in CON were fed with a basal diet consisting of concentrate mixture, green sorghum and paddy straw as per ICAR nutrient requirements, while the animals in BF100 and BF200 group were fed with same ration and supplemented with 0.75% (100 g/d) and 1.5% (200 g/d) bypass fat on DMI basis, respectively for 15 days pre-partum to 90 days post-partum. The dry matter intake, body condition score, milk yield and milk composition parameters like protein, lactose and SNF were not influenced by supplemental bypass fat. Milk fat percentage, production of 4% fat corrected milk (FCM), solid corrected milk (SCM) and energy corrected milk (ECM) increased quadratically with the increasing level of rumen protected fat in the diet. Feed efficiency (FCM/DMI) and energetic efficiency of milk production improved in a quadratic manner. Nutrient intake of DCP, TDN and digestibility of DM, CP, CF and NFE except EE remained statistically non-significant. The serum triglycerides, cholesterol and calcium level were higher in bypass fat-supplemented group. However, serum total protein and glucose level remained statistically at par. Thus, bypass fat supplementation at 0.75% of the DM intake (100 g/d) increased the milk fat percentage, FCM production and feed efficiency along with serum triglycerides and cholesterol level in lactating Surti buffaloes.